2019
DOI: 10.3390/nu11020390
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge Translation Performance in Health Professionals: Findings from the 2017 Unified Forces Preventive Nutrition Conference (UFPN)

Abstract: Background: Dietitians and other health care professionals must be able to translate findings from clinical trials into best treatment practices, a skill termed “knowledge translation”. This skill requires knowledge of treatment guidelines as well as the science underpinning treatment recommendations. Unsatisfactory knowledge translation of medical nutrition therapy (MNT) has been documented. Methods: Individuals registered to attend a leading national nutrition conference were asked to participate in an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The 15 indicators identified reflect the broad patient presentations commonly seen in acute health care settings and, being based on a thorough literature search and expert consensus, represent the current best evidence of nutritional risk in this setting. Nutrition evidence reported in the literature does not always align with nutritional therapy in clinical practice [ 31 ]. In the current study, application of the Delphi approach has clinically contextualised nutritional risk indicator literature, providing a superior level of understanding than would be achieved through considering the literature, or feedback from clinicians, in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The 15 indicators identified reflect the broad patient presentations commonly seen in acute health care settings and, being based on a thorough literature search and expert consensus, represent the current best evidence of nutritional risk in this setting. Nutrition evidence reported in the literature does not always align with nutritional therapy in clinical practice [ 31 ]. In the current study, application of the Delphi approach has clinically contextualised nutritional risk indicator literature, providing a superior level of understanding than would be achieved through considering the literature, or feedback from clinicians, in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritionists are considered the first line of contact with patients regarding nutritional genomics, and they are identified as prime candidates to provide advice on nutrition and genetics 22 . However, current nutrition and dietetics curricula do not include courses related to advanced human genetics, such as discussions of omics technologies, interpretation of genetic variation information, and legal, ethical, and social aspects of genetic information 22,23 . Education and training for nutrition professionals is relevant because the basic science and evidence surrounding nutritional genomics continues to develop, while clinical practice guidelines do not yet exist for gene-based nutrition advice and expectations for nutrition professionals are increasing in response to increasing demand for genetic testing 21 depth knowledge of the implications of genetic variation in the field of nutrition to promote health, both to prevent and manage disease is required, along with the skills to develop and implement therapeutic approaches that match diet and lifestyle to the client's genetic makeup 19 .…”
Section: The Relationship Between Knowledge and Selfconfidence Of Nut...mentioning
confidence: 99%
“…Practitioners should have direct experience with nutritional assessment that includes nutrigenetic testing 27 . To increase knowledge, selfconfidence and a sense of the importance of the profession in the field of nutritional genomics, educational innovation in the tertiary sector, both undergraduate and postgraduate levels must be encouraged as a main strategy in improving professional skills 22,23 . The lack of knowledge and confidence in genebased nutrition is mainly due to a lack of training and an unsupportive environment 28 .…”
Section: The Relationship Between Knowledge and Selfconfidence Of Nut...mentioning
confidence: 99%
“…In terms of the type of knowledge shared in KM, most studies to this date on food industry innovation processes involve knowledge coming from either food science or food engineering area, but not from nutritional sciences [17,18]. As such, it has been shown that dietitians and other nutrition professionals can improve their knowledge translation skills [19]. One study conducted in the context of a collaboration between ve nutrition researchers and ve food companies revealed positive attitudes toward collaboration together, but special attention must be paid to common goals, trust, prejudices, and collaboration agreements [20].…”
Section: Literature Reviewmentioning
confidence: 99%